Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's solve each of the given inequalities step-by-step and match them to their solutions:
1. [tex]\(-3x > -36\)[/tex]
To solve for [tex]\(x\)[/tex], we need to isolate [tex]\(x\)[/tex]. Start by dividing both sides by [tex]\(-3\)[/tex]. Remember that dividing by a negative number reverses the inequality sign.
[tex]\[ x < \frac{-36}{-3} \Rightarrow x < 12 \][/tex]
2. [tex]\(b + 5 > 23\)[/tex]
To solve for [tex]\(b\)[/tex], subtract 5 from both sides of the inequality:
[tex]\[ b > 23 - 5 \Rightarrow b > 18 \][/tex]
3. [tex]\(1 + 7n \geq -90\)[/tex]
To solve for [tex]\(n\)[/tex], subtract 1 from both sides of the inequality:
[tex]\[ 7n \geq -90 - 1 \Rightarrow 7n \geq -91 \][/tex]
Next, divide both sides by 7:
[tex]\[ n \geq \frac{-91}{7} \Rightarrow n \geq -13 \][/tex]
4. [tex]\(\frac{x}{2} - 2 > 1\)[/tex]
To solve for [tex]\(x\)[/tex], first add 2 to both sides of the inequality:
[tex]\[ \frac{x}{2} > 1 + 2 \Rightarrow \frac{x}{2} > 3 \][/tex]
Next, multiply both sides by 2:
[tex]\[ x > 3 \times 2 \Rightarrow x > 6 \][/tex]
Now let's match each inequality to its respective solution:
- [tex]\(-3x > -36\)[/tex] corresponds to [tex]\(x < 12\)[/tex]
- [tex]\(b + 5 > 23\)[/tex] corresponds to [tex]\(b > 18\)[/tex]
- [tex]\(1 + 7n \geq -90\)[/tex] corresponds to [tex]\(n \geq -13\)[/tex]
- [tex]\(\frac{x}{2} - 2 > 1\)[/tex] corresponds to [tex]\(x > 6\)[/tex]
Thus, the solutions are:
1. [tex]\(-3x > -36\)[/tex] ⟶ [tex]\(x < 12\)[/tex]
2. [tex]\(b + 5 > 23\)[/tex] ⟶ [tex]\(b > 18\)[/tex]
3. [tex]\(1 + 7n \geq -90\)[/tex] ⟶ [tex]\(n \geq -13\)[/tex]
4. [tex]\(\frac{x}{2} - 2 > 1\)[/tex] ⟶ [tex]\(x > 6\)[/tex]
1. [tex]\(-3x > -36\)[/tex]
To solve for [tex]\(x\)[/tex], we need to isolate [tex]\(x\)[/tex]. Start by dividing both sides by [tex]\(-3\)[/tex]. Remember that dividing by a negative number reverses the inequality sign.
[tex]\[ x < \frac{-36}{-3} \Rightarrow x < 12 \][/tex]
2. [tex]\(b + 5 > 23\)[/tex]
To solve for [tex]\(b\)[/tex], subtract 5 from both sides of the inequality:
[tex]\[ b > 23 - 5 \Rightarrow b > 18 \][/tex]
3. [tex]\(1 + 7n \geq -90\)[/tex]
To solve for [tex]\(n\)[/tex], subtract 1 from both sides of the inequality:
[tex]\[ 7n \geq -90 - 1 \Rightarrow 7n \geq -91 \][/tex]
Next, divide both sides by 7:
[tex]\[ n \geq \frac{-91}{7} \Rightarrow n \geq -13 \][/tex]
4. [tex]\(\frac{x}{2} - 2 > 1\)[/tex]
To solve for [tex]\(x\)[/tex], first add 2 to both sides of the inequality:
[tex]\[ \frac{x}{2} > 1 + 2 \Rightarrow \frac{x}{2} > 3 \][/tex]
Next, multiply both sides by 2:
[tex]\[ x > 3 \times 2 \Rightarrow x > 6 \][/tex]
Now let's match each inequality to its respective solution:
- [tex]\(-3x > -36\)[/tex] corresponds to [tex]\(x < 12\)[/tex]
- [tex]\(b + 5 > 23\)[/tex] corresponds to [tex]\(b > 18\)[/tex]
- [tex]\(1 + 7n \geq -90\)[/tex] corresponds to [tex]\(n \geq -13\)[/tex]
- [tex]\(\frac{x}{2} - 2 > 1\)[/tex] corresponds to [tex]\(x > 6\)[/tex]
Thus, the solutions are:
1. [tex]\(-3x > -36\)[/tex] ⟶ [tex]\(x < 12\)[/tex]
2. [tex]\(b + 5 > 23\)[/tex] ⟶ [tex]\(b > 18\)[/tex]
3. [tex]\(1 + 7n \geq -90\)[/tex] ⟶ [tex]\(n \geq -13\)[/tex]
4. [tex]\(\frac{x}{2} - 2 > 1\)[/tex] ⟶ [tex]\(x > 6\)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.